Multi-century (1800-2016) meteo-hydrological series for the Adda river basin (Central Alps) - Roberto Ranzi; Eleni Maria Michailidi; Massimo Tomirotti; Alice Crespi; Michele Brunetti; Maurizio Maugeri (PANGAEA, 2020)
This dataset contains high-quality series of meteo-hydrological variables reconstructed for the upper part of the Adda river basin (Central Italian Alps). In particular it includes: - the daily runoff time series of the Lake Como inflows and outflows, the longest for Italian Alps, reconstructed for the 1845-2016 period in the Adda river basin. The same series are also reported at monthly and annual (hydrological year, September-August) scales. - the monthly basin precipitation and temperature series reconstructed from in-situ observations for the 1800-2016 period. - the annual total basin precipitation series (hydrological year, September-August) for the 1846-2016 period with and without the correction for rain-gauge undercatch. - the annual and monthly estimated potential evapotranspiration for the basin (Thornthwaite equation) and annual losses (precipitation - inflows) for the 1846 - 2016 period (hydrological year, September-August).